Mechanism of fungal remediation of wetland water: Stropharia rugosoannulata as promising fungal species for the development of biofilters to remove clinically important pathogenic and antibiotic resistant bacteria in contaminated water - Sen, Keya; Llewellyn, Marina; Taheri, Babak; Turner, Robert J.; Berglund, Tanner; Maloney, Kellen (Frontiers in Microbiology, 2023)
Mushroom mycelia biofilters were evaluated for remediation of wetland water polluted with crow feces containing antibiotic resistant (AMR) bacteria. Three strains of fungi, Pleurotus ostreatus, Stropharia rugosoannulata and Pleurotus pulmonarius, were allowed to develop dense mycelia for 3-5 weeks on wood chips within cylindrical jars. Biofilter jars were incubated with wetland water (WW) obtained from a crow roost area that was additionally spiked with AMR bacteria isolated from previous crow fecal collections. E. coli, Staphylococcus aureus, Enterococcus faecium, Campylobacter jejuni, Klebsiella pneumoniae, Pseudomonas aeruginosa and Salmonella enteritidis were added at concentrations of 1500-3500 CFU/100 ml. Remediation was calculated from bacterial counts contributed by the spike and background water in CFU and in gene copy numbers. Stropharia and P. pulmonarius biofilters remediated six bacteria in the range of 43%-78% in one hour while P. aeruginosa was remediated at 24% and 0%, respectively. Incubation of biofilters with water for 24 hours showed Stropharia remediation to be superior relative to other tested fungi and for S. aureus it was 100%, E. faecium, 97%, C. jejuni, 59%, P. aeruginosa, 54%, E. coli, 65% and S. enteritidis, 27%. The mechanism of remediation was tested by removing the mycelium physically from the biofilter column after passage of water, followed by extraction of DNA. Association of bacterial DNA with the mycelia was demonstrated at GCN of 3500-54000/250 mg of mycelia by qPCR for the different bacteria except S. aureus and Salmonella. The results demonstrate that one of the ways mycelia biofilters can decrease pathogenic and AMR bacteria from water is by bio-filtration or bio-absorption of the bacteria. Fungal growth phase, close contact with bacteria and agitation were necessary for remediation. Overall, these results suggest that mushroom mycelia biofilters may provide a sustainable and effective approach for remediation of wetland water contaminated with pathogenic and antibiotic-resistant bacteria.